ETIKA PENDIDIK DAN PESERTA DIDIK DALAM PERSPEKTIF AL GHOZALI DAN IBN MISKAWAIH - M. Basori Alwi (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
This research aims to describe and analyze the ethics of educators and learners according to the perspective of Al Ghozali in the book of Ihya' Ulumuddin and Ibn Miskawaih in the book of Tahdzibul Akhlaq wa Thathirul Araq to develop ethical concepts in the field of education and as an effort to form the next generation of the nation that has ethics in accordance with educational goals. This research uses a qualitative descriptive approach and the type of research used is literature or library research. The technique of data collection is looking for data about things or variables in the form of notes, journals, books and others as such. Then the data is collected in the form of written records/ data. While in the data analysis used is content analysis (Content Analysis). The study of the thoughts of Al Ghozali and Ibn Miskawaih will certainly always be interesting, although both are both figures from the same religion, Namely Islam, but there is still an interesting side that concerns the similarities and differences between the two. This paper examines how the ethics of educators and learners according to Al Ghozali and Ibn Miskawaih. The ethics of educators that are strongly emphasized by Al Ghazali and Ibn Miskawaih is about the practice of science, both those that have not been and those that have been taught to learners. As for the learners themselves these two figures prioritize about the cleanliness of the soul and heart of learners from things or things that can prevent the entry of a science.